Strategi Pengembangan Usaha Melalui Pendekatan Business Model Canvas (Studi Pada Usaha Rumahan Achiella Cake) - Ramadhani, Saffa Archietya; Rizal, Syamsu; -, Azwar (Jurnal Administrasi Profesional, 2023)
The development of technology and information that is growing rapidly encouraging business people to increase work productivity and competitiveness in the industrial sector. At present, PT Chakra Jawara has implemented a system namely System Application and Products in Data Processing (SAP) since 2011 which is used to improve business performance and integrate all business activities through access to information data. SAP is one of the ERP (Enterprise Resource Planning) software products. This research was conducted to determine and analyze the application of SAP in the effectiveness of procurement. This study used qualitative research methods. Data collection was carried out through interviews and documentation, where the number of informants was 4 people. Data analysis was performed including data reduction, data presentation and verification. The results of this study indicate that the application of SAP in the effectiveness of procurement at PT Chakra Jawara is quite effective. This is seen through achieving the objectives of the SAP system which consists of increasing the speed, consistency and quality of the procurement activity process. The effectiveness of SAP application in the procurement can be seen through the achievement of established procurement principles and ethics, achievement of both SAP application objectives and procurement objectives such as time efficiency, appropriate price and specifications, security of information data in the SAP system, fair treatment to all parties involved, as well as information disclosure related to procurement activities. However, this SAP system still needs improvement to be able to run better and be able to reduce the constraints experienced.